Draft Genome Sequence of Brachybacterium phenoliresistens Strain W13A50, a Halotolerant Hydrocarbon-Degrading Bacterium - Wang, Xinxin (American Society for Microbiology, 2014)
Brachybacterium phenoliresistens strain W13A50 was isolated from a petroleum-contaminated saline site, which could degrade hydrocarbon under high salinity conditions. Here, we present 4.2-Mb draft genome sequence of this strain, which will provide insights into the diversity of Brachybacterium and the mechanism of hydrocarbon degradation in saline environments.